Knowledge Management Process for Community Health - Srithanee, Kitpapon; Manmart, Lampang (Journal of Health Science of Thailand, 2017)
The objective of this descriptive research was to study the knowledge management process in community health. The data were collected from the community that a combination of conventional medicine and traditional medicine was a forceful community with emphasis on the health care community which was related to the nation level of the two communities: Kam Pla Lai and Santisuk through interviewed via group discussions with the participation and involvement. The key informants were included those involvement of the community health in three sectors in professional, folk and popular for 14, 6 and 40 participants respectively including community activities for 9 months between May 2010 to January 2011. The results were shown that: (1) knowledge management for community health was not obvious and informal which was inserted in the health care process. The transfer of knowledge was the main process, (2) knowledge was in popular and folk which was inherent in term of people (tacit knowledge), e.g. composition of human body, cause of illness and health care from accumulated knowledge from the family and kinship. The importance of professional knowledge consisted of human body, illness, diagnosis and treatment. Consequently, the majority of drug usage, health promotion and disease prevention, and (3) the major of knowledge management process was knowledge transfer that transferred from professional sector and folk sector to popular sector were patients and relatives with public health volunteers who acted the mediate to integrated knowledge. The knowledge transfer methods were most of the social processes and collaboration in knowledge sharing. Therefore, the developing of knowledge transfer process should be used a variety of method that relates with knowledge content and focus on developing the more potential of public health volunteer.